Implikasi Hukum Terhadap Notaris yang Melakukan Keterlambatan Pendaftaran Jaminan Fidusia dalam Sistem Administrasi Hukum Umum Sebagai Pemegang Jaminan Fidusia - Haq, Sadida Amalia Izzatul; Aminah, Aminah (Legal Standing : Jurnal Ilmu Hukum, 2025)
One of the most important forms of collateral in Indonesia's financial sector is fiduciary security. When a debtor defaults on their payments, the civil law system gives creditors the authority to seize assets in order to get their money back. In order to guarantee that fiduciary certificates are legally legitimate, it is necessary to register them via the General Legal Administration System (AHU), as stated in Law Number 42 of 1999 on Fiduciary Security. On the other hand, notaries often cause delays in the registration procedure, which may impact creditors' rights and result in legal ramifications for the notaries themselves. The purpose of this research is to look at how the law protects creditors when notaries are late with registering fiduciary securities and what that means for their legal liability. The study examines applicable statutes, case law, and legal theories from a normative juridical perspective. According to the results, creditors risk having their preferred rights to the collateral object eroded and debtors' chances of abusing the fiduciary object increased if the registration process takes too long. Thus, in order to preserve creditors' legal rights, notaries must guarantee correct adherence to fiduciary registration processes.